2021
DOI: 10.3934/matersci.2021052
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulations of gradient cooling technique for controlled production of differential microstructure in steel strip or plate

Abstract: <abstract><p>Numerical studies were conducted to investigate the applicability of cooling strategies for controlledly producing a microstructure in the steel strip or plate, which changes as function of the plate length. In the numerical simulations, the water spray cooling was varied as function of the plate length and as a result, the different parts of the plate were cooled at different rates. We applied the previously developed numerical code where the transformation latent heat is coupled with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…For example, It has been recently shown that by applying local laser processing can enhance mechanical properties of achieved heterogeneous steel [1]. Previous experiments and numerical simulations [2] show that also differential cooling rates could be applied to controlledly create desired heterogeneous microstructure to the material. Furthermore, due to its effect on the mechanical properties, the microstructure development during processing [3][4][5][6] needs to be understood in detail in order to control it effectively.…”
Section: Introductionmentioning
confidence: 99%
“…For example, It has been recently shown that by applying local laser processing can enhance mechanical properties of achieved heterogeneous steel [1]. Previous experiments and numerical simulations [2] show that also differential cooling rates could be applied to controlledly create desired heterogeneous microstructure to the material. Furthermore, due to its effect on the mechanical properties, the microstructure development during processing [3][4][5][6] needs to be understood in detail in order to control it effectively.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously developed a coupled heat conduction and mean field (MF) phase transformation model [14][15][16][17], that has been applied for simulating austenite decomposition in cooling of a steel coil [15] as well as in slow cooling of low temperature ausformed steel, which leads to the formation of fine bainitic structure [18]. The mean field phase transformation model has been also used for simulating microstructure evolution to aid the design of induction hardening of a medium carbon pipeline material [19] where the model can be used for optimizing the cooling path and strategy so that desired fractions of different phases can be obtained [20,21] through the pipe thickness. Using this model, it is possible to quantitatively estimate the phase fraction and final hardness.…”
Section: Introductionmentioning
confidence: 99%